Activ C cervical disc replacement for myelopathy - McGonagle, L. (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: Cervical disc replacement is becoming an increasingly popular treatment option for cervical myelopathy. It retains motion at the affected segment, unlike anterior cervical discectomy and fusion. The aim of this study is to assess the outcomes of a series of patients who underwent Activ C disc replacement for cervical myelopathy. MATERIALS AND METHODS: A series of patients at the above Trust with clinical and radiological evidence of cervical myelopathy who were suitable for cervical disc replacement from 2007 to 2009 were included. Implants were inserted by one of two consultant surgeons {IMS, MO’M}. Patients were assessed preoperatively and at six, 12 and 24 months, postoperatively, with a visual analogue score (VAS) for neck and arm pain severity and frequency, the Neck Disability Index questionnaire (NDI) and the Centre for Epidemiologic Studies Depression questionnaire (CES-D). RESULTS: Ten patients underwent surgery between May 2007 and July 2009, 6 women, and 4 men. Average age was 54 years (40-64). Disc levels replaced were: four at C4-5; eight at C5-6; seven at C6-7. Three patients had one disc replaced, five patients had two discs replaced, and two patients had three discs replaced. The VAS for neck pain improved from 5.9 pre-operatively to 1.4-24 months postoperatively and the VAS arm pain improved from 5.4 to 2.6. The NDI improved from 51% preoperatively to 26.8% at 24 months postoperatively. The CES-D showed a slight increase from 19.5 preoperatively to 21.7 at 24 months, postoperatively. CONCLUSION: Cervical decompression and disc replacement improves pain and function in patients with cervical myelopathy. This benefit is maintained at 24 months post op, with no cases requiring revision.